2008
DOI: 10.1098/rsbl.2008.0373
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions by alpine plant communities in the Qinghai–Tibet Plateau

Abstract: using a closed chamber technique. Strong methane emission at the rate of 26.2G1.2 and 7.8G1.1 mg CH 4 m L2 h L1 was observed for a grass community in a Kobresia humilis meadow and a Potentilla fruticosa meadow, respectively. A shrub community in the Potentilla meadow consumed atmospheric methane at the rate of 5.8G1.3 mg CH 4 m L2 h L1 on a regional basis; plants from alpine meadows contribute at least 0.13 Tg CH 4 yr L1 in the Tibetan Plateau. This finding has important implications with regard to the regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 12 publications
1
54
3
Order By: Relevance
“…Model results indicated that plant-derived CH 4 emissions contribute 11.83 Tg CH 4 yr À1 over China, with 43% from forests, which account for 24% of the Chinese total CH 4 emissions (Xie et al, 2009). Cao et al (2008) suggested that local plants in alpine meadows account for at least 0.13 Tg CH 4 yr À1 on the Tibetan Plateau. These estimates may be included as potential explanations for the enigma of the recent regional and global CH 4 concentrations (Frankenberg et al, 2005;Heimann, 2011).…”
Section: Implications For the Regional Ch 4 Budgetmentioning
confidence: 99%
See 3 more Smart Citations
“…Model results indicated that plant-derived CH 4 emissions contribute 11.83 Tg CH 4 yr À1 over China, with 43% from forests, which account for 24% of the Chinese total CH 4 emissions (Xie et al, 2009). Cao et al (2008) suggested that local plants in alpine meadows account for at least 0.13 Tg CH 4 yr À1 on the Tibetan Plateau. These estimates may be included as potential explanations for the enigma of the recent regional and global CH 4 concentrations (Frankenberg et al, 2005;Heimann, 2011).…”
Section: Implications For the Regional Ch 4 Budgetmentioning
confidence: 99%
“…As rates of plant-derived CH 4 vary greatly across plant species in response to environmental stresses (Cao et al, 2008;Qaderi and Reid, 2009;Wang et al, 2009bWang et al, , 2008Wang et al, , 2011aWang et al, , 2011bWatanabe et al, 2012) and no in situ emissions of plant-derived CH 4 have been found, more emission data are needed under both controlled laboratory conditions and field conditions to elucidate the contribution of terrestrial plants to the global CH 4 budget. To the best of our knowledge, only one top-down evaluation has been conducted.…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…Two small electric fans were used to circulate the chamber air. Gas samples were collected in situ using 100 ml plastic syringes every 10 min over a 30 min period at local time from 09:00-11:00 to represent daily average flux as described by Cao et al [17]. The concentration of CH 4 in the gas samples was analyzed on a gas chromatograph (HP Series 4890D, Hewlett Packard, USA) within two days after sampling.…”
Section: Gas Sampling and Analysesmentioning
confidence: 99%